2014
DOI: 10.1002/14651858.cd008462.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Heparin versus 0.9% sodium chloride intermittent flushing for prevention of occlusion in central venous catheters in adults

Abstract: Heparin versus 0.9% sodium chloride intermittent flushing for prevention of occlusion in central venous catheters in adults. Cochrane Database of Systematic Reviews(10), CD008462.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 236 publications
0
13
0
Order By: Relevance
“…In the adult population, there have been several trials (Goossens et al, 2013, Schallom et al, 2012) a systematic review (Mitchell et al, 2009), and a Cochrane Review of the use of heparin versus normal saline to prevent occlusions in CVCs (Lopez-Briz et al, 2014). As evidence from adult studies is not directly transferable to paediatrics, a systematic review focused on infants and children is required.…”
Section: Introductionmentioning
confidence: 99%
“…In the adult population, there have been several trials (Goossens et al, 2013, Schallom et al, 2012) a systematic review (Mitchell et al, 2009), and a Cochrane Review of the use of heparin versus normal saline to prevent occlusions in CVCs (Lopez-Briz et al, 2014). As evidence from adult studies is not directly transferable to paediatrics, a systematic review focused on infants and children is required.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies show similar results, despite the difference in the concentration of heparin, which ranged from 10 to 5,000 IU/mL, used for blocking, over time to assess the permeability and type of the catheter. This heterogeneity is confirmed in a systematic review, which verified this variety of actions (8) . and 200 mg/mL vitamin C flush and considered occlusion without reflux as the primary outcome, concluding there is a difference between the use of heparin and ISS (p <0.04), choosing the heparin solution, more effective than ISS in maintaining the permeability of the analyzed CVC (13) .…”
Section: Discussionmentioning
confidence: 63%
“…Regarding the maintenance of venous devices in general, there is already a consensus on the use of 0.9% Isotonic Saline Solution (ISS) for flush. However, for the long-term solution of CVC blockade, there is no strong clinical evidence for the ISS recommendation on the heparin solution in reducing the incidence of occlusion (5,(7)(8)(9) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, some adverse effects are associated with heparin use, such as autoimmune-mediated heparin-induced thrombocytopenia, allergic reactions and the potential for bleeding complications following multiple, unmonitored heparin flushes (11). Also, a recent Cochrane review (12) has concluded that there is no good evidence that heparin flushing of central venous catheters is better than flushing with sterile saline solution.…”
Section: Discussionmentioning
confidence: 99%